Small-mammals from the Middle Pleistocene layers of the Sima del Elefante (Sierra de Atapuerca, Burgos, northwestern Spain) - J.M. LÓPEZ GARCÍA; H.A. BLAIN; R. DE MARFÀ I TAILLEFER; A. GARCÍA; J. MARTINELL; M.L. BENNASAR FÉLIX; G. CUENCA BESCÓS (Geologica Acta, 2011)
The Sima del Elefante site, located in the Sierra de Atapuerca (Burgos, Spain), is an important Pleistocene archaeopalaeontological locality that has been excavated every year since 1996. At least two main infill phases have been identified: a first (TELRU) early Pleistocene phase that has provided a rich faunal assemblage, various stone tools and the earliest human remains from western Europe; and a second phase (TEURU) attributed to the Middle Pleistocene. In this paper, for the first time we present a description of the TEURU small-mammal assemblage and its subsequent biochronological, palaeoenvironmental and palaeoclimatic implications. The small-mammal assemblage is highly diverse and comprises at least 17 species: 3 insectivores (cf. Erinaceus sp., Crocidura sp. and Sorex sp.); 4 chiropters (Rhinolophus ferrumequinum, Rhinolophus gr. euryale-mehelyi, Myotis gr. Myotisoxygnathus and Miniopteurs schreibersii); 9 rodents (Myodes glareolus, Microtus arvalis, Microtus agrestis, Iberomys brecciensis, Terricola cf. atapuerquensis, Arvicola sp., Apodemus sylvaticus, Eliomys quercinus and Allocricetus bursae) and 1 lagomorph (Oryctolagus sp.). Such an association suggests a late Middle Pleistocene age (ca. 250-350 ka), a patchy landscape dominated by humid meadows and woodland areas, and mild climatic conditions. These results are compared with other proxies, such as the herpetofauna, malacofauna, large-mammals and charcoals, providing a new scenario for the climatic and environmental conditions that prevailed during the latest Middle Pleistocene in the Sierra de Atapuerca.